3D Building Modeling Training and Assistance in Making Mockups as an Effort to Improve the Skills of Archasena Tulungagung Community Members: Pelatihan 3D Modelling Bangunan dan Pendampingan Pembuatan Maket Sebagai Upaya Peningkatan Keterampilan Anggota Komunitas Archasena Tulungagung - Diyah Ayu Saputri; Ryski Dwi Pratowo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
This Community Service (PkM) activity was motivated by the lack of skills in implementing 2D designs into 3D mockups that pay attention to architectural rules in the Archasena Tulungagung community. This PkM activity was carried out by Architecture Lecturers and Architecture HMPs at Bhinneka PGRI University, Tulungagung, East Java by providing 3D modeling training and assistance in making mockups. Training and mentoring are carried out by first providing material to increase participants' understanding before making the product. The output of this PkM activity is a 3D mockup product whose manufacture considers architectural principles. The activities that produce this product are an effort to improve the skills of members of the Archasena Tulungagung Community.